Asymmetries of poverty: why global burden of disease valuations underestimate the burden of neglected tropical diseases. - Charles H King; Anne-Marie Bertino (Public Library of Science (PLoS), 2008)
The disability-adjusted life year (DALY) initially appeared attractive as a health metric in the Global Burden of Disease (GBD) program, as it purports to be a comprehensive health assessment that encompassed premature mortality, morbidity, impairment, and disability. It was originally thought that the DALY would be useful in policy settings, reflecting normative valuations as a standardized unit of ill health. However, the design of the DALY and its use in policy estimates contain inherent flaws that result in systematic undervaluation of the importance of chronic diseases, such as many of the neglected tropical diseases (NTDs), in world health. The conceptual design of the DALY comes out of a perspective largely focused on the individual risk rather than the ecology of disease, thus failing to acknowledge the implications of context on the burden of disease for the poor. It is nonrepresentative of the impact of poverty on disability, which results in the significant underestimation of disability weights for chronic diseases such as the NTDs. Finally, the application of the DALY in policy estimates does not account for the nonlinear effects of poverty in the cost-utility analysis of disease control, effectively discounting the utility of comprehensively treating NTDs. The present DALY framework needs to be substantially revised if the GBD is to become a valid and useful system for determining health priorities.